Collagenase Treatment in Dupuytren Contractures: A Review of the Current State Versus Future Needs. Issue 1 (June 2016) - Degreef, Ilse
Abstract Dupuytren disease is highly prevalent and the finger contractures can be very extensile, compromising the patients' hand function. To restore full function, contractures have been addressed by cutting the causative strands for nearly 200 years, ever since Baron Guillaume Dupuytren demonstrated his technique at the beginning of the nineteenth century. Surgery can be minimal (fasciotomy) or quite invasive (fasciectomy and even skin replacement). However, in the last decade translational research has introduced the non-surgical technique of enzymatic fasciotomy with collagenase injections. Now, finger contractures can be released with single injections on monthly intervals, to address one joint contracture at a time. However, in hands affected with Dupuytren contractures to the extent that the patient calls for treatment, most often more than one joint is involved. In surgical treatment options all contracted joints are addressed in a single procedure. Nevertheless, extensile surgery withholds inherent risks of complications and intense rehabilitation. Today, the minimally-invasive method with enzymatic fasciotomy by collagenase injection has demonstrated reliable outcomes with few morbidities and early recovery. However, single-site injection is todays' standard procedure and multiple joints are addressed in several sessions with monthly intervals. This triggers a longer recovery and treatment burden in severely affected hands even though surgery is avoided. Therefore, further treatment modalities of collagenase use are explored. Adjustments in the treatment regimes' flexibility and collagenase injections addressing more than one joint contracture simultaneously will improve the burden of multiple sessions and, therefore, enzymatic fasciotomy may become the preferred method in more extensile Dupuytren contractures. In this independent review, the challenge of Dupuytren disease affecting a single versus multiple joints is presented. The pros and cons of collagenase use are weighed, founded by the available scientific background. The demands and options for collagenase in future treatment regimens for extensile Dupuytren contractures are discussed.